2011
DOI: 10.1098/rspb.2011.0652
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inbreeding, genetic dissimilarity and phenotype on male reproductive success in a dioecious plant

Abstract: Pollen fate can strongly affect the genetic structure of populations with restricted gene flow and significant inbreeding risk. We established an experimental population of inbred and outbred Silene latifolia plants to evaluate the effects of (i) inbreeding depression, (ii) phenotypic variation and (iii) relatedness between mates on male fitness under natural pollination. Paternity analysis revealed that outbred males sired significantly more offspring than inbred males. Independently of the effects of inbreed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 73 publications
1
23
1
Order By: Relevance
“…We extracted genomic DNA from dried leaves from 258 field‐collected individuals using the Qiagen Biospring DNA kit. Genotypes were obtained for nine nuclear microsatellite regions previously isolated in S. latifolia : Sil 1, Sil 4, Sil 6, Sil 8 (Teixeira & Bernasconi 2007) and Sillat 06, Sillat 07, Sillat 08, Sillat 25 Sillat 28 (Austerlitz et al. 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We extracted genomic DNA from dried leaves from 258 field‐collected individuals using the Qiagen Biospring DNA kit. Genotypes were obtained for nine nuclear microsatellite regions previously isolated in S. latifolia : Sil 1, Sil 4, Sil 6, Sil 8 (Teixeira & Bernasconi 2007) and Sillat 06, Sillat 07, Sillat 08, Sillat 25 Sillat 28 (Austerlitz et al. 2011).…”
mentioning
confidence: 99%
“…PCR was carried out in a final volume of 10 μL that contained 5–10 ng of template DNA, 2 μ m of each of the forward and reverse primers, and 1 × Qiagen HotStarTaq Plus Master Mix. PCR amplification was performed in a Biometra thermal cycler, following the conditions described for each locus in Austerlitz et al. 2011).…”
mentioning
confidence: 99%
“…; Austerlitz et al. ; Rebernig et al. ), as well as to the expectation that pollen from selfers should be less competitive than pollen from outcrossers (Mazer et al.…”
Section: Discussionmentioning
confidence: 97%
“…HUDSON 1998 experimental work has shown that the pollen received while visiting a male flower is deposited on the next three female flowers (LABOUCHE and BERNASCONI 2010). This limits the extent of dispersal, as shown also by a paternity analysis (AUSTERLITZ et al 2012). Also seed dispersal between established populations is likely to be limited in this species were seeds are gravity dispersed.…”
Section: Discussionmentioning
confidence: 99%
“…These chapters reveal the interesting result of differential inferences based upon molecular marker origin, and the failure of current population genetic models to accommodate such heterogeneities. I present a model in Chapter 3 based upon the identification of inbreeding avoidance in the focal species (AUSTERLITZ et al 2012;RICHARDS et al 1999) as well as differential explanatory power of molecular markers derived from heterogeneous genomic regions for identifying Heterozygosity Fitness Correlations (or HFCs) (OLANO-MARIN et al 2011).…”
Section: Introductionmentioning
confidence: 99%